Flexible Working Arrangement dan Pengawasan Langsung terhadap Efektivitas Kerja Karyawan Field Education Consultant Ruangguru Region Jakarta Barat - Tangerang - Darajat, Nazmah Pauziah; Erry Sunarya; Faizal Mulia Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The aim of this research is to determine the effect of flexible working arrangements and direct supervision on employee work effectiveness. This research was carried out at PT. Ruang Raya Indonesia (Ruangguru) is part of the Field Education Consultant (FEC) Ruangguru region, West Jakarta - Tangerang. The method used in this research is descriptive and associative research with a quantitative approach. The sampling technique in this research used saturated sampling. The sample taken in this research was 60 employees. Data analysis techniques use validity and reliability tests, classical assumption tests, multiple linear regression including correlation coefficients, coefficients of determination, research model testing and research hypothesis testing. The results of research using the coefficient of determination test (R2) show that flexible working arrangements and direct supervision on work effectiveness are 38.06% while the remaining 61.94% is influenced by other factors outside this research. Based on the multiple correlation coefficient test, the R value is 0.617, which means there is a strong relationship between flexible working arrangements and direct supervision on work effectiveness. The results of the F test are the value of Fcount 17.558 ≥ Ftable 3.15, indicating that Fcount is greater than Ftable. The flexible working arrangement variables and simultaneous direct supervision have a significant influence on the work effectiveness variable. Keywords: Work Effectiveness, Flexible Work Arrangement, Direct Supervision